Monitoring of Biodistribution and Persistence of Conditionally Replicative Adenovirus in a Murine Model of Ovarian Cancer Using Capsid-Incorporated mCherry and Expression of Human Somatostatin Receptor Subtype 2 Gene - Igor P. Dmitriev; Elena A. Kashentseva; Kenneth H. Kim; Qiana L. Matthews; Stephanie S. Krieger; Jesse J. Parry; Kim N. Nguyen; Walter J. Akers; Samuel Achilefu; Buck E. Rogers; Ronald D. Alvarez; David T. Curiel (Molecular Imaging)
A significant limiting factor to the human clinical application of conditionally replicative adenovirus (CRAd)-based virotherapy is the inability to noninvasively monitor these agents and their potential persistence. To address this issue, we proposed a novel imaging approach that combines transient expression of the human somatostatin receptor (SSTR) subtype 2 reporter gene with genetic labeling of the viral capsid with mCherry fluorescent protein. To test this dual modality system, we constructed the Ad5/3Δ24pIXcherry/SSTR CRAd and validated its capacity to generate fluorescent and nuclear signals in vitro and following intratumoral injection. Analysis of 64 Cu-CB-TE2A-Y3-TATE biodistribution in mice revealed reduced uptake in tumors injected with the imaging CRAd relative to the replication-incompetent, Ad-expressing SSTR2 but significantly greater uptake compared to the negative CRAd control. Optical imaging demonstrated relative correlation of fluorescent signal with virus replication as determined by viral genome quantification in tumors. Positron emission tomography/computed tomography studies demonstrated that we can visualize radioactive uptake in tumors injected with imaging CRAd and the trend for greater uptake by standardized uptake value analysis compared to control CRAd. In the aggregate, the plasticity of our dual imaging approach should provide the technical basis for monitoring CRAd biodistribution and persistence in preclinical studies while offering potential utility for a range of clinical applications.